(untitled) (Bangladesh Journal of Pharmacology, 2021)
This study was to compare the performance of the students (future pres-cribers) of four medical colleges using three modules on rational prescribing. Marks obtained (out of 35) in ‘student-centered learning’ approach in first and second assessment were 28.3 ± 3.4 and 23.7 ± 4.2 respectively, which is significantly (p<0.01) higher than the control (12.9 ± 6.4 and 10.0 ± 6.1). Marks obtained (out of 40) in ‘problem-based learning’ approach in first and second assessment were 38.2 ± 1.5 and 32.0 ± 2.4 respectively, which is significantly (p<0.01) higher than the control (23.2 ± 3.8 and 22.7 ± 2.4). Marks obtained (out of 40) in ‘integrated learning’ approach in first and second assessment were 32.0 ± 1.8 and 28.8 ± 2.0 respectively, which is significantly (p<0.01) higher than the control (20.9 ± 2.09 and 14.3 ± 3.7). Though the marks obtained in control and all three intervention groups in first assessment was significantly (p<0.05) reduced in the second assessment. Thus, student-centered, problem based and integrated learning approaches are more effective than traditional method.